Carbamazepine-induced Stevens-Johnson syndrome/toxic epidermal necrolysis overlap in a Filipino with positive HLA-B75 serotype. (17th July 2018) - Capule, Francis; Tragulpiankit, Pramote; Mahasirimongkol, Surakameth; Wichukchinda, Nuanjun; Jittikoon, Jiraphun; Alentajan-Aleta, Lara Theresa; James Barit, Jay-V; Casanova-Gutierrez, Josephine; Cabral-Lim, Leonor; Baltazar Reyes, Jose Paciano; Roa, Francisca; San Gabriel, Katrina Faith; et al.
Abstract : Stevens-Johnson syndrome (SJS) and toxic epidermal necrolysis (TEN) are two related mucocutaneous disorders with different severities. Although the incidence is low, SJS and TEN are life-threatening and predominantly drug-induced conditions. There is a strong relationship between the HLA-B*1502 allele and carbamazepine-induced SJS and TEN in different Southeast Asian populations. Here, we report a case of Filipino with SJS/TEN overlap probably induced by carbamazepine. The condition was treated with hydrocortisone followed by prednisone. The HLA-B*1502 allele was not found in this case. The patient tested positive for the HLA-B75 serotype, suggesting that carbamazepine-induced SJS/TEN may be serotype specific. Establishing the genotype before initiation of the drug may be advantageous for some patients and will aid physicians in determining the optimal drug therapy. Prevention of adverse drug reactions (ADR) may be done if pharmacists and other healthcare professionals work as a multidisciplinary ADR team to ensure that safe medication practices are realised.